2017
DOI: 10.1213/ane.0000000000002453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Intravenous Dexamethasone Added to Caudal Local Anesthetics to Improve Postoperative Pain: A Systematic Review and Meta-analysis With Trial Sequential Analysis

Abstract: Intravenous dexamethasone prolongs the analgesic duration of caudal anesthesia. Trials to investigate the effectiveness of a lower dose of the dexamethasone in prolonging analgesic effects would be of interest. Further trials with a low risk of bias are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Many published reports in different surgical fields have described the analgesic effect of steroids. [23][24][25][26][27] In the present study, patients receiving dexamethasone also reported less pain and needed less oxycodone for 5 postoperative days. A study by Clayburgh et al 28 showed that extended perioperative corticosteroid use after transoral robotic surgery for initial treatment of oropharyngeal squamous cell carcinoma decreased the length of hospital stay, although postoperative pain was minimally affected.…”
Section: Discussionsupporting
confidence: 55%
“…Many published reports in different surgical fields have described the analgesic effect of steroids. [23][24][25][26][27] In the present study, patients receiving dexamethasone also reported less pain and needed less oxycodone for 5 postoperative days. A study by Clayburgh et al 28 showed that extended perioperative corticosteroid use after transoral robotic surgery for initial treatment of oropharyngeal squamous cell carcinoma decreased the length of hospital stay, although postoperative pain was minimally affected.…”
Section: Discussionsupporting
confidence: 55%
“…Steroids may have many perioperative effects on complications. Recent investigations including a systematic review and meta‐analysis confirmed that intravenous dexamethasone prolongs analgesia from a caudal . We assessed dexamethasone's effect, if any, on perioperative complications in part as a search for a possible cause of increased complications, ie, could the improved analgesia or altered edema be a cause for the increased complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have compared the relative efficacy and adverse effects of various adjuvants such as alpha-2 agonists (clonidine [9] and dexmedetomidine [8]), N-methyl-D-aspartate (NMDA) agonists (ketamine [10] and magnesium [11]), opioids (fentanyl, morphine, and tramadol [12]), corticosteroids (dexamethasone [13][14]), and acetylcholine esterase inhibitors (neostigmine) [12]. However, such individual pairwise meta-analyses cannot provide all adjuvants' comparative effectiveness and relative rankings.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Various adjuvants have been shown to enhance caudal blocks with varying degrees of success. A multitude of clinical trials and meta-analyses have analyzed the efficacy of different adjuvants such as alpha-2 agonists (clonidine [9] and dexmedetomidine [8]), N-methyl-D-aspartate (NMDA) agonists (ketamine [10] and magnesium [11]), opioids (fentanyl, morphine, and tramadol [12]), corticosteroids (dexamethasone [13][14]), and acetylcholine esterase inhibitors (neostigmine) [12]. The European Society of Regional Anesthesia and Pain Therapy (ESRA) and the American Society of Regional Anesthesia and Pain Medicine (ASRA) joint committee practice advisory on pediatric regional anesthesia [3] provides specific recommendations on many adjuvants but given a plethora of recent studies; this advisory is likely already outdated.…”
Section: Introduction and Background Introductionmentioning
confidence: 99%